An open secret in porcine acute myocardial infarction models: The relevance of anaesthetic regime and breed in ischaemic outcomes - Solanes, Núria; Bobi, Joaquim; Arrieta, Marta; Jimenez, Francisco Rafael; Palacios, Carmen; Rodríguez, Juan José; Roqué, Mercè; Galán-Arriola, Carlos; Ibañez, Borja; Freixa, Xavier; García-Álvarez, Ana; Sabaté, Manel; et al. (Frontiers in Veterinary Science, 2022)
Large animal models of acute myocardial infarction (AMI) play a crucial role translating novel therapeutic approaches to patients as denoted by their use in the right-before-human testing platform. At present, the porcine model of AMI is used most frequently as it mimics the human condition and its anatomopathological features accurately. We want to describe to, and share with, the translational research community our experience of how different anaesthetic protocols and pig breeds can dramatically modify the outcomes of a well-established porcine model of closed-chest AMI. Our group has extensive experience with the porcine model of reperfused AMI and, over time, we reduced the time of ischemia used to induce the disease from 90 to 50 minutes to increase the salvageable myocardium for cardioprotection studies. For logistical reasons we changed both the anaesthetic protocol and the pig breed used but these resulted in a dramatic reduction in the size of the myocardial infarct, to almost zero in some cases, and the cardiac function was preserved. Therefore, we had to re-validate the model by returning to 90 minutes of ischemia. Here we report the differences in infarct size and cardiac function, measured by different modalities, for each combination of anaesthetic protocol and pig breed we have used. Furthermore, we discuss these combinations and the limited literature pertaining to how these two factors influence the cardiac function and infarct size in the porcine model of AMI.